Influence of negative ions on the stoichiometry and structure of carbon nitride films deposited by reactive magnetron sputtering - Wieschhoff, Christian; Theile-Rasche, Chantal; Wang, Fuzeng; Prib, Michael; Moldt, Viktoria Daniela Dorothea; Grundmeier, Guido; Salas, Nieves López; de los Arcos de Pedro, Maria Teresa (Journal of Applied Physics)
Magnetron-sputtered CNx thin films are primarily employed as hard, low-friction protective and tribological coatings, as solar cells, and for catalytic applications. Lower growth rates and a reduced N content, favoring graphitic sp2 structures, hinder industrial scalability due to prolonged deposition times and produce softer, less dense films with inferior hardness, elasticity, and wear resistance. Carbon nitride films deposited by magnetron sputtering exhibit growth behavior strongly influenced by plasma–surface interactions. However, nitrogen resputtering and reduced film growth rates are commonly attributed to chemical etching by positive ions. We propose an additional, unreported power-dependent mechanism involving negative ions formed at the carbon target. These ions are accelerated through the plasma sheath, reaching the substrate with high kinetic energy and inducing both chemical and physical resputtering. This effect is localized to the geometrical projection of the target, as shown by spatially resolved analysis: ellipsometry reveals thickness reduction, and x-ray photoelectron spectroscopy and Raman spectroscopy indicate nitrogen depletion within this region. Correlation between stoichiometry and structural signatures confirms the decisive role of negative ions in modifying the film composition and microstructure. At the same time, the composition of the gas mixture exerts only a minor effect.

Role of Irradiance in Light-Activated In 2 O 3 Gas Sensors: Why More Light Is Not Always Better - Voth, Sven; Zhao, Zhenyu; Baier, Dominik; Glass, Alexandra; Elgabarty, Hossam; Sandberg, Oskar J.; Grundmeier, Guido; Tiemann, Michael; Smått, Jan-Henrik; Anttu, Nicklas; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian (ACS Sensors)

Influence of deposition temperature and thickness of ALD-TiO2 on planar perovskite solar cell performance - Qudsia, Syeda; Weiss, Alexander; Sirkiä, Saara; Wang, Fuzeng; Rosqvist, Emil; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Halme, Janne; Kemell, Marianna; Smått, Jan-Henrik (Applied Surface Science)

„I matter!?“ – Eine Studie zur Vorbildfunktion von Lehrkräften im inklusiven Klassenzimmer. Vortrag auf der 90. Sektionstagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) in der DGfE. Thema: „Wissen|schaf[f]t|Ordnung? Zur Dynamik von Wissensordnungen in erziehungswissenschaftlicher Forschung, Gesellschaft und Pädagogik“. (angenommen) - Letzel-Alt, V; Hassani, S; Löper, Marwin Felix; Hellmich, Frank

Quenching During Thermomechanical Joining Using Friction Spun Joint Connectors - Nordieker, Ansgar Bernhard; Homberg, Werner (Transactions of the Indian Institute of Metals)
Abstract Mechanical joining processes have played an increasingly important role in the manufacturing of modern lightweight structures due to a greater variety of materials. The growing number of joining tasks requires a large number of joining elements. Friction spun joint connectors (FSJC) offer an innovative approach that meets the growing demand for flexibility. This process combines rotational movement and axial force to create targeted friction heating, enabling the production of FSJCs and the joining of various sheet metal materials. The shape of the FSJC can be optimally adapted to the joining situation in question, providing a significant advantage in terms of process chain versatility. This paper investigates FSJCs made of the steel grades C45E+C (1.1191) and 115CrV3 (1.2210), the effect of in situ quenching during the joining process. The influences of the essential parameters of rotational speed, feed rate, and FSJC length on the mechanical properties after quenching are being focused on and compared to similar conditions during joining without quenching. At the same time, the material change is analyzed to determine the effect of different alloy approaches on hardness profiles and strength characteristics in cross-tensile testing. For this purpose, systematic test series with varying process parameters are conducted and evaluated using hardness measurements and cross-tensile tests.

Informal approaches to predictive modeling: fostering data literacy and critical engagement through decision tree construction - Fleischer, Franz Yannik; Biehler, Rolf (ZDM – Mathematics Education)
Abstract This study investigates how secondary students construct and evaluate decision trees in an open exploratory task using CODAP. By analyzing students’ tree products and oral self-reports, we identified different data-based and context-based approaches to predictor selection and stopping criteria. Students engaged with key ideas of predictive modeling, including classification, model construction, accuracy, generalization, and interpretability. Informal exploration offered rich opportunities for subsequent teaching by enabling students to begin reconstructing central technical ideas and critical tensions of predictive modeling through diverse but meaningful reasoning approaches.

Long-time asymptotics for the heat kernel and for heat equation solutions on homogeneous trees - Papageorgiou, Efthymia (2603.11232)
We study the large-time behavior of the continuous-time heat kernel and of solutions to the heat equation on homogeneous trees. First, we derive sharp asymptotic formulas for the heat kernel as $t\to\infty$. Second, using them, we show that solutions with initial data in weighted $\ell^1$ classes, asymptotically factorize in $\ell^p$ norms, $p\in[1,\infty]$, as the product of the heat kernel, times a $p$-mass function, dependent on the initial condition and $p$. The $p$-mass function is described in terms of boundary averages associated with Busemann functions for $p<2$, while for $p\ge 2$, it is expressed through convolution with the ground spherical function. For comparison, the case of the integers shows that a single constant mass determines the asymptotics of solutions to the heat equation for all $p$, emphasizing the influence of the graph geometry on heat diffusion.

Uncentred maximal operators with respect to half balls on Damek--Ricci spaces - Chalmoukis, Nikolaos; Meda, Stefano; Papageorgiou, Efthymia; Santagati, Federico (arXiv:2604.27839)
In this paper we study a variant of the uncentred Hardy--Littlewood maximal operator on Damek--Ricci spaces in which balls are replaced by suitable half balls. Perhaps surprisingly, such modified maximal operator has better boundedness properties than the classical one. In particular, it satisfies an $L\log L$ endpoint estimate and it is bounded on $L^p$ for every $p$ in $(1,∞]$.

Reducing Compute Waste in LLMs through Kernel-Level DVFS

Unveiling Barriers to Recycling with a Focus on Design: An Ishikawa Diagram-Based Approach with Industrial Application - Rohde, Katharina; Gonzalez, Barbara Fernandez; Budde, Finn Lukas; Ott, Manuel; Mozgova, Iryna; Mendibe, Alain Alonso (Safe and Sustainable Value Creation by Design - Proceedings of the 21st Global Conference on Sustainable Manufacturing)
The circular economy offers decisive advantages over the currently prevalent linear economy in industry. Firstly, the reuse of products, individual parts and material reduces the need for new production or generation and the associated consumption of energy and resources. Secondly, it helps to avoid the generation of waste. Early consideration of circular economic principles in product development processes is essential to specifically promote reuse, reparability and recycling. Efficient recycling of assemblies requires well-defined strategies. However, various challenges hinder the efficiency of technical recycling processes in industrial applications. This paper presents an Ishikawa (fishbone) diagram-based approach to systematically identify and categorize these influences. The method is implemented within an industrial framework, highlighting key obstacles such as material composition, design constraints, use of technology, framework conditions, economic limitations and regulatory challenges. By applying a scenario analysis, this approach examines potential future developments and their impact on recycling-oriented design choices. This helps to identify critical influencing factors and supports the development of resilient and sustainable industrial practices. This framework will serve as the foundation for developing an automated approach to circular design, enabling industries to more effectively integrate sustainability into their processes and adapt to changing environmental demands.

Digital product passports and the challenge of product structure granularity: A decision-making framework for the level of DPP integration - Rohde, Katharina; Budde, Finn Lukas; Patrício, Bárbara; Ferreira, Tânia; Gonçalves, Ana; Ott, Manuel; Mozgova, Iryna (Proceedings of the Design Society)
Political goals, emerging EU sustainability regulations, and industrial digitalization are driving the introduction of Digital Product Passports (DPPs) to enhance transparency, traceability, and compliance across product life cycles. However, the appropriate granularity of DPP integration across product architectures remains ambiguous. This paper introduces a structured, decision-oriented framework that links product structure, regulatory relevance, and information depth to define consistent DPP levels, supporting both industry implementation and future standardization.
Keywords: digital product passport; product architecture; circular economy; information granularity; decision-making framework

Insights into an Iranian Internet Shutdown - Anonymous, Anonymous; Niere, Niklas; Graf Lange, Felix; Somorovsky, Juraj
In June 2025, Iran enacted a nationwide Internet shutdown, culminating its already strict censorship apparatus. While Internet shutdowns happen regularly, insights into these shutdowns are notoriously difficult to obtain: their timing is hard to predict, and measurements are often impossible. In this paper, we present unique measurements surrounding Iran’s 2025 Internet shutdown in June, which we acquired during a regular analysis of Iran’s censorship apparatus. We contextualize our findings of Iranian DNS, HTTP, TLS, and QUIC censorship during the shutdown with measurements from platforms such as Cloudflare Radar and user reports. Our measurements show that Iranian censorship changed before and after the shutdown, marking preparation and recovery periods. For instance, QUIC censorship went into effect before and stayed in effect after the shutdown, while DNS over TCP censorship was only present briefly before the shutdown and resumed working afterwards. We also measured general network instabilities, especially for UDP, after the shutdown and the disabling of certain middleboxes. Our findings indicate that the Iranian censor enforced its shutdown using fine-grained techniques instead of relying on an all-or-nothing blackout. We advertise for continued measurements of the Iranian censor and hypothesize that future shutdowns in censoring countries could be detected during their preparation phase.

Reducing Compute Waste in LLMs through Kernel-Level DVFS

Leveraging extreme-scale simulation data: a workflow framework for multidisciplinary simulator integration - Gräßler, Iris; Döhner, Niklas (Proceedings of the Design Society)
ABSTRACT: Engineers simulate system behavior to support decisions in product engineering. Leveraging such engineering simulation data in strategic product planning can support idea generation and early evaluation of design alternatives and limitations. However, limited resources and expertise hinder broader uptake in strategic product planning. This paper investigates simulator integration into automated workflows and key processing components to enable simulation without in-depth expertise. This approach improves strategic product planning by creating data-based decision support.
Keywords: simulation-based design; design tools; multi-/cross-/trans-disciplinary approaches; simulation data reuse

Design for circular behaviour: a literature-based conceptual model - Jagnow, Jan; Stöhr, Bernd; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: The transition to a circular economy requires products that encourage circular consumer behaviour. Despite the central role of designers in this transition, the design for circular behaviour (DfCB) approach remains under-explored. This paper presents a literature-based conceptual model explaining which factors need to be in place, and how they interrelate, in order for designers to facilitate circular behaviours through product design. By pointing out gaps in the current state, future research directions are suggested to foster the establishment of DfCB.

Creating, Commemorating, and Challenging an American Origin Story: The Many Uses of 1776 - Hartmann, Alexandra; Purk, Antonia (Amerikastudien/American Studies)

PLM und Datenökosysteme für eine MBSE-basierte zirkuläre Wertschöpfung - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens (Nachhaltigkeit in der Produktentwicklung)

Leveraging Large Language Models in Engineering Design and Product Development: A Snapshot - Altun, Osman; Ott, Manuel; Meihöfener, Niclas; Budde, Finn; Mozgova, Iryna (Procedia Computer Science)

Ressourceneffiziente Produktentwicklung: Synergien von Leichtbau und Nachhaltigkeit in Optimierungsprozessen - Mozgova, Iryna; Altun, Osman; Ott, Manuel; Rohde, Katharina (Nachhaltigkeit in der Produktentwicklung)

Neue Mikrodaten zu Unternehmensinsolvenzen in Deutschland: Die insol Datenbank - Rahali, Mahdi; Beyer, Bianca; Gassen, Joachim; Geschonke, Sebastian